HUBUNGAN ANSIETAS DENGAN KUALITAS TIDUR PADA PENDERITA TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS SITOPENG KOTA CIREBON - Erlina; Dewi Erna Marisa; Ahmad Syaripudin (Jurnal Kesehatan Mahardika, 2020)
The number of tuberculosis sufferers is increasing, 13.6%, an increase in 2016 in West Java. Cirebon City is one of the 3 cities with the highest TB prevalence, in West Java in 2017. sufferers often experience coughs that interfere with the fulfillment of sleep needs. Prolonged tuberculosis treatment often causes anxiety for patients. This study aims to determine the relationship between anxiety and sleep quality in tuberculosis patients. This study used a descriptive correlation research design with a cross sectional approach. The population in this study were tuberculosis patients in the Sitopeng Public Health Center in Cirebon, the sample in this study was 32 respondents and the sampling technique used in this study was the total sampling instrument used in the form of a questionnaire sheet. The results of univariate analysis, 24 respondents (75.0%) experienced no anxiety, 2 respondents (6.3%) mild anxiety, 2 respondents (6.3%) moderate anxiety, 2 respondents (6.3%) severe anxiety and 2 respondents (6.3%) severe anxiety %). Sadang patients with tuberculosis who experienced sleep disorders as many as 26 respondents (81.3%) experienced good sleep quality, and those who experienced poor sleep quality were 6 respondents (18.8%). Bivariate analysis with the results of statistical tests using the chi square test showed the p-value (p = 0.009; α = 0.05), there was a relationship between anxiety and sleep quality. The conclusion of this study is that the higher the anxiety, the worse the sleep quality in tuberculosis sufferers.